PENGARUH KINERJA KEUANGAN TERHADAP MANAJEMEN LABA PERBANDINGAN PERUSAHAAN YANG TERKONEKSI DAN TIDAK TERKONEKSI POLITIK - Fitri Nur Indahsari; Tri Jatmiko Wahyu Prabowo (Diponegoro Journal of Accounting, 2021)
This study aims to determine the relationship between financial performance and earnings management actions by comparing companies that are have politically connected & not connected. Company performance is the result of company work that explains the company's financial operating activities. The company's financial capability can be seen from the profits obtained and presented in the company's financial statements. The results of this study will show whether the company's financial performance is related to earnings management actions in companies that are have politically connected & not connected. This study used secondary data which was annual reports retrieved from Indonesia Stock Exchange (IDX) website. This study used purposive sampling method. Population in this study were company listed on the Indonesia Stock Exchange in 2017-2018. The research method used in this study was linear regression. This study used stakeholder theory and agency theory to formulate hypotheses that lead to the results of the analysis. The results showed that financial performance had a significant effect on earnings management for a sample of all companies. Meanwhile, the results of the research on financial performance for companies that were have politically connected and not connected had no significant effect on earnings management. The results of this study also indicate that the value of corporate financial performance and earnings management for companies with have political connections is higher than for companies that are not have politically connected.